2014
DOI: 10.1158/0008-5472.can-13-3369
|View full text |Cite
|
Sign up to set email alerts
|

ATR Inhibitors VE-821 and VX-970 Sensitize Cancer Cells to Topoisomerase I Inhibitors by Disabling DNA Replication Initiation and Fork Elongation Responses

Abstract: Camptothecin and its derivatives, topotecan and irinotecan are specific topoisomerase I (Top1) inhibitors and potent anticancer drugs killing cancer cells by producing replication-associated DNA double-strand breaks, and the indenoisoquinoline LMP-400 (indotecan) is a novel Top1 inhibitor in clinical trial. To develop novel drug combinations, we conducted a synthetic lethal siRNA screen using a library that targets nearly 7,000 human genes. Depletion of ATR, the main transducer of replication stress came as a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
110
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 145 publications
(119 citation statements)
references
References 48 publications
7
110
0
2
Order By: Relevance
“…In the same study VX-970 increased sensitivity to cisplatin in six out of seven NSCLC PDX models [94]. In addition, ATR inhibitors have been shown to increase sensitivity to topoisomerase I inhibitors in colorectal cancer cell lines in vitro and in vivo [95], rationalising the combination of ATR inhibitors and topotecan in early phase clinical trials in SCLC. Summary of DNA damage pathways and therapeutics (Fig.…”
Section: Vx-970mentioning
confidence: 85%
“…In the same study VX-970 increased sensitivity to cisplatin in six out of seven NSCLC PDX models [94]. In addition, ATR inhibitors have been shown to increase sensitivity to topoisomerase I inhibitors in colorectal cancer cell lines in vitro and in vivo [95], rationalising the combination of ATR inhibitors and topotecan in early phase clinical trials in SCLC. Summary of DNA damage pathways and therapeutics (Fig.…”
Section: Vx-970mentioning
confidence: 85%
“…Nevertheless, how replication stress can be measured in normal and cancer cells remains elusive. Because multiple ATRi and Chk1i are being tested in clinical trials for cancer therapy (Foote et al, 2013; Josse et al, 2014; Karp et al, 2012; Ma et al, 2013; Sausville et al, 2014; Seto et al, 2013), understanding the mechanisms of action and unique properties of these inhibitors may help to guide their applications in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…In vivo studies using both VE-821 and VX-970 showed robust results. Indeed, these two ATR inhibitors synergized with radiotherapy and gemcitabine in pancreatic cancer xenograft models [76, 77] and with irinotecan in a colorectal cancer model [79]. Nowadays, different clinical trials are ongoing against solid tumors to assess the safety, tolerability, and pharmacokinetics of VX-970 in combination with cytotoxic chemotherapy (NCT02157792, NCT02595931, NCT02567422, and NCT02595892).…”
Section: Introductionmentioning
confidence: 99%